The co-creation of trans microcelebrity: a case study of Nikkie de Jager - Homant, Ellie (AoIR Selected Papers of Internet Research, 2026)
In January 2020, beauty vlogger Nikkie de Jager (better known by her username NikkieTutorials) publicly came out as a trans woman, after more than a decade-long career on YouTube during which she passed as a cisgender, heterosexual woman, and under duress of a blackmailer who threatened to leak her “secret” identity. Far from ending her career, de Jager’s disclosure propelled her to greater success in the cutthroat creator economy, increasing her celebrity status. In this article, I argue that de Jager leveraged her coming-out to bolster her performance of authenticity as a microcelebrity, reaffirming and deepening her intimacy with her audience. This dialogic intimacy is central to the performance of microcelebrity. While previous studies have theorized the strategies that creators use to perform microcelebrity, little attention has been paid to the role of the audience in microcelebrity. I argue that microcelebrity is a strategy of performance that is co-constructed with the audience, making it distinct from parasocial relationships.